Prototype Alat Pengaman Mobil Berbasis Internet of Things (IoT) - Ifni Joi; Yustini; Roza Susanti; Efendi; Fadli Fadilah Islami (Ikatan Ahli Informatika Indonesia, 2021)
Car security system is something that needs to be considered in everyday life. Often car owners keep an eye on their cars parked in public places. The car is equipped with a security system from the manufacturer but it is only local or only in the form of an alarm in the car, so it cannot be heard from afar by the car owner. So we need a car security that can tell the car owner if there is a thief or break the glass where the car owner is. This IoT-based car safety device uses experiments, namely by conducting trials if there is a car thief in front of the car door. This tool uses a PIR sensor to detect human movement in front of the car door and a vibration sensor to detect vibrations at the car door. Both sensors are used to detect thieves or break cars. The microcontroller used is the Node MCU ESP8266 which will process the second input and send a message to telegram if there is a car thief. Buzzer is used as a local alarm if there is a car thief. PIR sensor can detect humans within a range of 1 meter more than 1 meter does not detect humans. While the vibration sensor will be high if there is a vibration on the car door. The response time of the MCU Node sending a message to the owner's cell phone via telegram is 6.05 seconds. This security tool works well in detecting thieves or breaking car windows.